2016
DOI: 10.4137/cmo.s38204
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Paclitaxel versus Three-Weekly Paclitaxel in Recurrent Platinum-Resistant Epithelial Ovarian and Peritoneal Cancers: A Phase III Study

Abstract: INTRODUCTIONTreatment of recurrent platinum-resistant ovarian and peritoneal cancers represents a therapeutic challenge. The aim of this Phase III prospective study was to compare the survival benefits, objective response rate, and toxicities among patients treated by weekly paclitaxel with those who underwent three-weekly paclitaxel in recurrent platinum-resistant ovarian and peritoneal cancers.METHODPatients with recurrent platinum-resistant ovarian and peritoneal cancer were allocated to receive either week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Prior retrospective study of patients with BRCA mutated ovarian cancer has demonstrated that paclitaxel, as a monotherapy, produced high response rates regardless of DD or Q3W dosing; those data also suggested increased activity in platinum-sensitive disease [ 29 ]. In patients with platinum resistant disease, however, it has been shown that DD paclitaxel resulted in better survival benefit and quality of life [ 30 ]. Here, our study showed that DD paclitaxel was associated with longer median PFS versus Q3W dosing in HRP and BRCA wt subgroups, but this effect was observed to a lesser extent in patients with a deleterious BRCA m or HRD.…”
Section: Discussionmentioning
confidence: 99%
“…Prior retrospective study of patients with BRCA mutated ovarian cancer has demonstrated that paclitaxel, as a monotherapy, produced high response rates regardless of DD or Q3W dosing; those data also suggested increased activity in platinum-sensitive disease [ 29 ]. In patients with platinum resistant disease, however, it has been shown that DD paclitaxel resulted in better survival benefit and quality of life [ 30 ]. Here, our study showed that DD paclitaxel was associated with longer median PFS versus Q3W dosing in HRP and BRCA wt subgroups, but this effect was observed to a lesser extent in patients with a deleterious BRCA m or HRD.…”
Section: Discussionmentioning
confidence: 99%
“…Weekly paclitaxel is a common standard treatment option for women with platinum-resistant/refractory ovarian cancer. The median PFS is approximately 4.0-7.0 months, demonstrating an urgent need to develop agents that can delay taxane resistance [30,31]. The addition of antiangiogenic agents, such as bevacizumab (a VEGFA antibody), pazopanib (a multi-targeted tyrosine kinase inhibitor of VEGF receptors), and trebananib (an anti-angiopoietin), to weekly paclitaxel significantly improves PFS [6,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, over 80% of patients with advanced ovarian cancer who achieve a complete response with conventional first-line chemotherapy will develop recurrent disease [ 5 ]. Despite modest response rates for all regimens (20–30%), dose-dense paclitaxel is a preferred agent in treating platinum-resistant recurrence [ 6 8 ]. Virtually all relapsed patients will die of disease, highlighting the pressing need for novel therapies.…”
Section: Introductionmentioning
confidence: 99%